Customer Shopping Behavior on E-Commerce Effectiveness Using the Information System Success Theory Approach - Maliana Puspa Arum; Lina Fatimah Lishobrina; Muhammad Eka Purbaya; Tsabitatul Iffah; Olivia Cristianti (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2023)
In addressing the purpose of this research, it seeks to unravel the intricacies of payment systems in e-commerce, particularly focusing on the challenges posed by the indirect nature of transactions. The design and methodology of the study involve a comprehensive examination of customer perceptions and concerns, emphasising payment security and privacy in the digital landscape. This investigation stems from recognising that security is a linchpin for the successful development of Internet-based payment systems. Within the discourse of e-commerce, customer apprehensions regarding the security of their payment and financial information, encompassing details like credit card transaction numbers, are prevalent. As the e-commerce market in Indonesia experiences rapid growth, exemplified by the leadership of Tokopedia, the competition among companies and organisations intensifies. The endeavour to satisfy customers becomes a formidable challenge for many, underscoring the need for nuanced insights into the factors influencing customer satisfaction. Adopting the Information System Success Theory as a theoretical framework, this study posits that customer concerns about the payment system significantly impact the perceived quality of service. In this context, quality serves as a yardstick for measuring effectiveness by delving into the intricate layers of customer satisfaction. The research employs Structural Equation Modelling (SEM) as the chosen methodology, engaging with the perspectives of 100 respondents to derive meaningful conclusions. Despite its contributions, the study acknowledges its limitations, including the inherent subjectivity in customer perceptions. Nevertheless, the implications drawn from this research carry significance for the ongoing refinement and enhancement of e-commerce payment systems, providing valuable insights for practitioners, researchers, and policymakers navigating the dynamic intersection of technology and consumer satisfaction in the digital age.